2010
DOI: 10.1007/s00453-010-9442-9
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Finding Graph Roots with Girth Conditions

Abstract: Graph G is the square of graph H if two vertices x, y have an edge in G if and only if x, y are of distance at most two in H . Given H it is easy to compute its square H 2 , however Motwani and Sudan proved that it is NP-complete to determine if a given graph G is the square of some graph H (of girth 3). In this paper we consider the characterization and recognition problems of graphs that are squares of graphs of small girth, i.e. to determine if G = H 2 for some graph H of small girth. The main results are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…This leads to the open problem of determining the complexity of H-SQUARE ROOT when H is the class of graphs of treewidth at most 2. We also Graphs of girth at least 4 [11] NP-complete…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the open problem of determining the complexity of H-SQUARE ROOT when H is the class of graphs of treewidth at most 2. We also Graphs of girth at least 4 [11] NP-complete…”
Section: Discussionmentioning
confidence: 99%
“…Adamaszek and Adamaszek [1] proved that if a graph has a square root of girth at least 6, then this square root is unique up to isomorphism. Farzad, Lau, Le and Tuy [10] showed that recognizing graphs with a square root of girth at least g is polynomial-time solvable if g ≥ 6 and NP-complete if g = 4. The missing case g = 5 was shown to be NP-complete by Farzad and Karimi [9].…”
Section: Existing Resultsmentioning
confidence: 99%
“…Significant advances have also been made on the complexity of H-Square Root. Previous results show that H-Square Root is polynomial-time solvable for the following graph classes H: trees [28], proper interval graphs [23], bipartite graphs [22], block graphs [26], strongly chordal split graphs [27], ptolemaic graphs [24], 3-sun-free split graphs [24], cactus graphs [18], cactus block graphs [12] and graphs with girth at least g for any fixed g ≥ 6 [14]. The result for 3-sun-free split graphs was extended to a number of other subclasses of split graphs in [25].…”
Section: Introductionmentioning
confidence: 99%
“…On the negative side, H-Square Root remains NP-complete for each of the following classes H: graphs of girth at least 5 [13], graphs of girth at least 4 [14], split graphs [23], and chordal graphs [23]. All known NP-hardness constructions involve dense graphs [13,14,23,31], and the square roots that occur in these constructions are dense as well. This, in combination with the aforementioned polynomial-time results, leads to our underlying research question:…”
Section: Introductionmentioning
confidence: 99%